(S)He's Gotta Have It: Emotion Regulation, Emotional Expression, and Sexual Risk Behavior in Emerging Adult Couples. Issue 3 (3rd July 2017) - Rizor, Asha; Callands, Tamora; Desrosiers, Alethea; Kershaw, Trace
ABSTRACT: Emotion regulation and emotional expression may be important factors which contribute to sexual risk behavior among emerging adults, yet research exploring their relation is limited. Further, the influence of a romantic partner is unclear. The current study aims to a) investigate association between emotional difficulties and sexual risk behavior (e.g., sexual compulsivity and sensation-seeking) and b) explore the influence of a romantic partner on individual sexual risk. Participants were 49 couples ( n = 98) participating in a randomized control pilot intervention. Results demonstrated that individual and partner emotional difficulties were associated with sexual risk behavior. Results did not vary by gender.